Model Kebijakan Penal Dalam Upaya Pencegahan Kejahatan Seksualterhadap Anak (Sexual Crime On Child) - Rizal, Muhammad Syamsu (2017)
Violence against children has reached at its peak. Many children who are innocent should be dispelled hopes to achieve goals due to violence especially sexual violence. Government to move quickly to make the protection of children by establishing a legislation which contains three additional punishment that is planting a chip, the announcement identity of the offender and chemical castration that the perpetrators have a deterrent effect on potential perpetrators and not to do the same thing. However, a sentence of imprisonment and the application of additional penalties is still considered unable to give deterrent effect to the perpetrators. Thus, in this study, the approach used is the juridical-empirical to know how far the penalties that apply to reduce the number of levels of crime against children as well as models of penal policy that is how that should be applied to the perpetrators in order to provide a deterrent effect. From this research, there are still high levels of violent crimes against children and the effectiveness of the new penalty is still questionable. Because this punishment is still relatively new in law enforcement in Indonesia.